“Laminar Mixed Convection Correlations for an Isothermal Cylinder in Cross Flow at Different Angles of Attack - Abu-Hijleh , Bassam (1999)
The problem of laminar mixed convection from an isothermal cylinder is solved numerically. The average Nusselt number is calculated at different values of Reynolds number, Grashof number, and incoming free stream angle of attack. Different correlations are presented, each valid for a specific range of Reynolds number, buoyancy parameter, and angle of attack.